Application of Next-Generation Sequencing in Infections After Allogeneic Haematopoietic Stem Cell Transplantation: A Retrospective Study - Zhang, Xiaoying; Li, Yun; Yin, Jin; Xi, Bixin; Wang, Na; Zhang, Yicheng (Frontiers in Cellular and Infection Microbiology, 2022)
This retrospective study aimed to determine the characteristics of infection and diagnostic efficacy of next-generation sequencing (NGS) in patients with fever after allogeneic hematopoietic stem cell transplantation (allo-HSCT). A total of 71 patients with fever after HSCT were enrolled in this study. Compared with conventional microbiological test (CMT), we found that the sensitivity of NGS versus CMT in peripheral blood samples was 91.2% vs. 41.2%, and that NGS required significantly less time to identify the pathogens in both monomicrobial infections (P=0.0185) and polymicrobial infections (P= 0.0027). The diagnostic performance of NGS was not affected by immunosuppressant use. Viruses are the most common pathogens associated with infections. These results indicated that the sensitivity, timeliness, and clinical significance of NGS are superior for the detection of infections. Although NGS has the advantage of identifying a wide range of potential pathogens, the positive rate is related closely to the sample type. Therefore, we recommend that, in the clinical application of NGS to detect pathogens in patients after allo-HSCT, an appropriate sample type and time should be selected and submitted to improve the positive rate and accuracy of NGS. NGS holds promise as a powerful technology for the diagnosis of fever after HSCT.